Health and Safety in Indian Tourism: A Comprehensive Review - KUSHWAH, Vinita; VYAVAHARE, Yogesh (Journal of Environmental Management and Tourism; Vol 16 No 2 (2025): JEMT, Volume XVI, Issue 2(78), Summer 2025DO - 10.14505/jemt.v16.2(78).09, 2025)
The health and safety of tourists are vital for a sustainable and positive tourism experience. In India, the growing tourism industry offers immense opportunities but also presents serious challenges in managing health and safety. This review paper examines the current situation by analyzing recent literature and official reports. It highlights improvements in health infrastructure and safety awareness but notes persistent risks such as infectious diseases like malaria and dengue, especially in rural areas. Many healthcare facilities are still under-equipped to meet tourist demands. Safety concerns also include crime, poor transportation infrastructure, and natural disasters. The study identifies key areas for improvement, such as stricter enforcement of health and safety regulations, better training for tourism professionals, and investment in emergency response systems. Additionally, greater public awareness and preparedness among tourists and local communities is essential. These findings contribute to sustainable tourism development in India by offering actionable insights to improve tourist well-being and safety.